Exogenous application of biostimulant in zucchini (Cucurbita pepo L.) subjected to salt stress (Revista Ciência Agronômica, 2020)
The physiological potential of seeds is one of the main factors that should be considered at the plantingof a crop. This study aimed to evaluate the exogenous application of biostimulant in zucchini, cv. Caserta Italiana, undersalt stress conditions. For this, the experiment was divided into two parts. The first one was carried out in the laboratory,using a completely randomized experimental design, in a 5 x 3 factorial scheme (biostimulant doses and seed soakingtimes), with four replicates of 25 seeds. The second one was carried out in a greenhouse, in a completely randomizedexperimental design, in a 2 x 6 factorial scheme with four replicates, corresponding to two levels of irrigation watersalinity (0.5 and 5.0 dS m-1) and six forms of biostimulant application in seeds and leaves. Treatment of zucchini seeds,cv. Caserta Italiana, with biostimulant (Stimulate®) at the dose of 10 mL L-1, for 8 hours, proved to be viable and resultedin vigorous seedlings when irrigated with 5.0 dS m-1 saline water.